The Need of Career Counseling Awareness for Self Actualization among Students and Parents at a Secondary level of the Public schools of Karachi - Shazia Inayat Ali; Anjum Bano Kazmi (Al-Qanṭara, 2023)
This study that aims to identify “The Need of Career Counseling Awareness for Self Actualization among Students and Parents at Secondary Level of the Public Schools of Karachi.” The study highlights the importance of awareness about the Career Counseling programs which help to enhance the self-Actualization among the students and parents at the secondary level students. The research based on Mixed Methodology Explanatory Sequential method and for that first Quantitative data was collected and analyzed using the SPSS, one-way ANOVA for testing sample and on the basis of quantitative analysis develop semi-structured questions and analysis through the thematically approach. The results showed that Majority students and parents were not aware about the career opportunities and Also, students don’t had any goals for their career development which effects on student and parents decisions and satisfaction level.